Mapping the Influence of Organizational Culture on Entrepreneurial Orientation - Sri Palupi Prabandari; Ida Yulianti; Muhammed Jawo; Irma Kurniasari (www.amertainstitute.com, 2024)
This study explores the impact of organizational culture on entrepreneurial orientation (EO) through a comprehensive literature review. EO is a critical dimension of organizational strategy, encompassing innovation, risk-taking, and proactiveness, which are essential for maintaining competitiveness and driving business success. The findings indicate that organizational cultures fostering innovation, calculated risk-taking, and entrepreneurial values significantly enhance EO development. These cultural attributes provide an environment that encourages creativity, supports experimentation, and promotes proactive strategies for identifying and capitalizing on new opportunities. The study identifies recurring themes in the literature, such as the positive correlation between supportive cultural values and improved organizational performance. Companies that cultivate an entrepreneurial culture are better positioned to respond to market changes, innovate, and sustain long-term growth. Moreover, the research points to gaps in existing studies, including the need for deeper exploration of how different cultural dimensions interact with EO across various industries and organizational sizes. Practical implications for managers include the importance of embedding entrepreneurial values into organizational culture through leadership practices, employee training, and resource allocation. By doing so, managers can create an environment conducive to innovation and adaptability. Future research should further investigate cross-cultural variations and longitudinal effects of entrepreneurial culture on organizational success.